Nuclear Medicine Procedures in Diagnosis of Infective Endocarditis - Demir, H.; Canbaz, F.C.; Durmuş-Altun, G.D.; Özdemir, E.; Özdemir, S.; Şen, F. (Galenos Publishing House, 2020)
Infective endocarditis (IE) is described as infection of endocardial surfaces of heart and if available prosthesis materials. Despite all up to date developments in diagnosis and treatment of its, IE is mortal and morbid disease. IE causes numerous non-specific symptoms and findings in patients. Currently, various difficulties are observed in diagnosis and differential diagnosis of IE. Duke criteria is used for supporting of diagnosis. Also, echocardiography, computerized tomography (CT), positron emission tomography (PET)/CT, magnetic resonance, labeled leukocyte scintigraphy, blood culture, polymerase chain reaction investigations are used. Although, histopathological diagnosis is gold standard. In this procedure guideline nuclear medicine methods (PET/CT and labeled leukocyte scintigraphy) will be handled that used more frequently in recent years for diagnosis of IE. © Telif Hakkı 2020 Türkiye Nükleer Tıp Derneği / Nükleer Tıp Seminerleri, Galenos Yayınevi tarafından yayınlanmıştır.
Enfektif Endokardit Tanısında Nükleer Tıp Uygulamaları
Keywords: F-18 Fluorodeoxyglucose; IE; In-111 Oxine; Labeled Leukocyte Scintigraphy; PET/CT; Tc-99m Hexamethylpropyleneamine Oxime